Linking hydrologic regime, rainfall and leaf litter fall in a riverine forest within the ramsar site humedales Chaco (Argentina) - Casco, Sylvina Lorena (2015)
The input of leaf litter from riparian vegetation could be affected by changes in precipitation and modifications to the hydrological regime. We analyse the pattern of leaf litterfall at the community scale as well as the breakdown rate in a mixed gallery forest that covers the levees of the Paraná River oxbow lake. Litterfall was collected biweekly for 4 years that represents different rainfall and hydrologic regimes of the Paraná River including flood and prolonged drought: 1996-1997 (PA), 1999-2000 (PB), 2005-2006 (PC) and 2007-2008 (PD). To analyse leaf breakdown, litter bags were incubated on the forest floor during flooding conditions (FFo) and dry conditions (DFo) and in the oxbow lake (FOx). The total annual leaf litterfall were 8.97, 11.15, 10.42 and 14.43 tn ha1 yr1 for PA, PB, PC and PD, respectively. Our results suggest that with the increasing severity of the dry season and decreasing hydrologic connectivity, the annual leaf litterfall increases, whereas its seasonal pattern does not change. Regardless of the seasonal pattern of rainfall and hydrological regime in each study period, leaf fall occurred throughout the year, and the peakwas recorded between August and October. Leaves decomposed fastest in FOx, and the leaf breakdown on the forest floor was slower during flooding conditions than in dry conditions. Regular floods are natural occurrences that do not affect the leaf production of the Paraná mixed forest, and the leaf processing depends on the oxygen concentrations. Prolonged droughts led to high annual leaf production, which is mainly processed within this forest.